Theater on the Tracks: the performance of Boca de Ouro within a train in the suburban region of Salvador (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Theater director Fernando Guerreiro, one of the most important directors in the history of theater in Bahia, resized the relationship between the artist and the city by putting together the show Boca de Ouro, by Nelson Rodrigues, inside a moving train in the Subúrbio Ferroviário de Salvador. With site-specific characteristics, the traveling piece became a landmark in the recent memory of the performing arts in the Bahian capital. In addition to being shown in an unusual space and moving theater from the center to the periphery, it also gained a formative and social mobilization character, through the dialogue between the director and the cast with community leaders and the holding of art workshops for the residents of the suburban region.
Keywords: Site-specific; Boca de Ouro; Nelson Rodrigues; Theaterin Bahia